2011
DOI: 10.1021/jf202364v
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Phytochemicals and Antioxidant Activities of a Purple Tomato (Solanum lycopersicum L.)

Abstract: A newly developed nongenetically modified purple tomato V118 was investigated for its phytochemical compositions and antioxidant activities. A highly efficient and sensitive UPLC method was developed for both the phenolics and carotenoids, which showed that in addition to the phytochemicals commonly known for tomatoes, V118 had a unique composition of anthocyanins. The total carotenoid content of V118 was 234.78 μg/g dry weight (DW), and the total phenolic content was 659.11 mg GAE/100 g DW. The antioxidant ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
2
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 48 publications
6
67
2
4
Order By: Relevance
“…The observed TPCs were in the middle of the range of 1.2 to 22 µg·g −1 fresh weight that has been reported for processed tomatoes [38]. The observed ORAC values were in the upper range of 12-323 µmol·TE·g −1 dry weight reported by Li et al [37] for processed tomatoes and higher than reported in Zhou and Liangli [39].…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…The observed TPCs were in the middle of the range of 1.2 to 22 µg·g −1 fresh weight that has been reported for processed tomatoes [38]. The observed ORAC values were in the upper range of 12-323 µmol·TE·g −1 dry weight reported by Li et al [37] for processed tomatoes and higher than reported in Zhou and Liangli [39].…”
Section: Discussionsupporting
confidence: 44%
“…Fruit internal quality is defined by parameters such as the content of fat, lipids, proteins, vitamins, mineral nutrients and pigments [20], as well as health related parameters such as TPC and ORAC [37]. In this study, the sugar content of the investigated fruits was generally high and, as to be expected, the time of harvest had the greatest effect on fruit sugar content.…”
Section: Discussionmentioning
confidence: 56%
“…The color characteristics of CIE L*, a*, b* were calibrated against a standard white plate. Data were the average of triplicate measures on equidistant points of the plant powder (Li et al, 2011). Plant powder instead of actual plant parts were used in this experiment for better reproducibility and uniformity.…”
Section: Colorimetric Studymentioning
confidence: 99%
“…Long extraction and pre-treatment steps, including freeze drying (Gautier et al 2008;Giuntini et al 2008;Gómez-Romero et al 2010;Le Gall et al 2003;Sánchez-Rodríguez et al 2011;Spencer et al 2005;VanderRest et al 2006), 15-24 h maceration (Ferreres et al 2010;Li et al 2011;Sánchez-Rodríguez et al 2011;Slimestad and Verheul 2005;Slimestad et al 2008), SPE clean-up (Le Gall et al 2003;Li et al 2011;Vallverdú-Queralt et al 2011), or multiple extraction cycles (Gautier et al 2008;Simonetti et al 2005;Spencer et al 2005;VanderRest et al 2006). ii.…”
Section: Introductionmentioning
confidence: 99%